KELAYAKAN USAHA TANI TUMPANG SARI KETELA UNGU (Ipomoea batatas L.) DENGAN BUNGA KOL (Brassica oleracea var. botrytis l.) (STUDI KASUS DI DESA KARANGLO, KECAMATAN TAWANGMANGU, KABUPATEN KARANGANYAR) - Hendro Setyo Nugroho; Mahananto; M.Th Handayani (JURNAL ILMIAH AGRINECA, 2020)
Sweet potatoes are generally planted in monoculture, but it is not uncommon for farmers to apply a system of intercropping sweet potatoes with other plants that are shorter than sweet potatoes. Intercropping is a growth of two or more plants together on one land. Cauliflower is a type of leaf vegetable that is cultivated by farmers, especially in the highlands with an altitude of 1,000 - 2,000 masl. Basic methods used in the study was descriptive. Research locations in Karanglo Village, Tawangmangu Sub-district, Karanganyar Regency because that location is the one of producer of sweet potatoes purple variety in Tawangmangu Sub-district. Data used in this research are secondary and primary data. Results of feasibility studies the analysis with an average land area 0,14 hectare that is total costs Rp 10.208.081,38, revenue Rp 19.150.220,00, income 14.576.654,00. with a profit Rp 8.942.138,62. Farming of Intercropping Purple Cilantro And Cauliflower feasibility to be developed because revenue (Rp 19.150.220) > BEP revenue (Rp 261.574,07), R/C (1,87) ? 1, ?/C (87,59 %) > prevailing bank interest 10,25%,), and labor productivity (Rp 369.909,60)> prevailing wage rate (Rp 80.000,00).